Off-Time Work-Related Smartphone Use and Bedtime Procrastination of Public Employees: A Cross-Cultural Study - Hu, Wei; Ye, Zeying; Zhang, Zhang (Frontiers in Psychology, 2022)
While previous studies have examined the negative effects of work-related smartphone use after hours, little is known about whether and how it influences employees’ unhealthy sleep behavior (i.e., bedtime procrastination). Drawing on the ego depletion theory, this study explored the effects of work-related smartphone use after hours on bedtime procrastination. To further uncover potential cross-cultural differences, a sample of 210 public employees from the United States and 205 public employees from China were used. Results via path analysis revealed that off-time work-related smartphone use positively influenced bedtime procrastination via the mediating role of self-control depletion. These findings were consistent between the United States and Chinese sample; however, off-time work-related smartphone use after hours increased the likelihood of self-control depletion more strongly in the United States than in China. The implications of our findings for both theory and practice were discussed.